Pengaruh Struktur Modal dan Profitabilitas terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Variabel Intervening pada Perusahaan Food and Beverage yang Terdapat di BEI Tahun 2019-2023 - Andriani, Rahma Syifa; Wijaya, Ronni Andri; Sari, Silvia (ARZUSIN, 2025)
This study aims to determine the effect of capital structure, profitability on company value with dividend policy as an intervening variable in food and beverage companies listed on the Indonesia Stock Exchange. This study uses a quantitative method. The population in this study were all those listed in food and beverage with a total of 95 companies listed on the Indonesia Stock Exchange for the period 2019-2023. The sample in this study that met the criteria and was determined by the purposive sampling method so that a total sample of 18 food and beverage companies was obtained with a research period of 5 years. The analysis method used is multiple linear regression analysis using the Statistical Package for the Social Sciences (Spss) version 26. The results of this study indicate that capital structure does not have a significant effect on dividend policy, profitability does not have a significant effect on dividend policy, capital structure does not have a significant effect on company value, profitability has a significant effect on company value, dividend policy has an effect on company value, in addition, the results of the study simultaneously show that capital structure has a significant effect on company value through dividend policy and profitability does not have a significant effect on company value through dividend policy.